Microvascularization of corpus luteum of bovine treated with equine chorionic gonadotropin. Issue 9 (19th June 2015) - Bezerra Moura, Carlos Eduardo; Rigoglio, Nathia Nathaly; Braz, Janine Karla França S.; Machado, Marcello; Baruselli, Pietro S.; De Carvalho Papa, Paula
ABSTRACT This study aimed to evaluate the morphological changes in microvascular density and corpus luteum (CL) vascularization in cows treated with eCG during stimulatory and superovulatory protocols. Sixteen cows were synchronized and divided into three groups: control (n = 6), stimulated (n = 4) and superovulated (n =6), one was submitted to estrous synchronization (ES) and received no eCG (control), and those that were submitted to ES and received eCG before or after follicular deviation (superovulation and stimulation of the dominant follicle, respectively). Ovulation was synchronized using a progesterone device‐based protocol. After six days of ovulation, the cows were slaughtered and the ovaries and CL were collected. The CLs were processed and photomicrographs were taken under light microscopy to assess the vascular volume density (Vv) by stereology, and scanning electron microscopy (SEM) was used to perform ultrastructural analysis of the microvasculature. The Vv in stimulated and superovulated cows significantly increased (P ≤ 0.0001) when compared to control, indicating that the eCG is able to induce angiogenic activity in bovine CL. However, no significant differences were observed between stimulated and superovulated cows. The SEM demonstrated ratings indicative of angiogenesis, marked by several button‐shaped projections in the capillaries, and the presence of more dilated capillaries in CL treated with eCG. These morphological findings are evidence of an angiogenic effect of the eCG treatment in CL of cows. Microsc. Res. Tech. 78:747–753, 2015. © 2015 Wiley Periodicals, Inc.